Cortical relapses in multiple sclerosis. (August 2016) - Puthenparampil, Marco; Poggiali, Davide; Causin, Francesco; Rolma, Giuseppe; Rinaldi, Francesca; Perini, Paola; Gallo, Paolo
Background: Multiple sclerosis (MS) is a white and grey matter disease of the central nervous system (CNS). It is recognized that cortical damage (i.e. focal lesions and atrophy) plays a role in determining the accumulation of physical and cognitive disability that is observed in patients with progressive MS. To date, an association of cortical lesions with clinical relapses has not been described. Results: We report clinical and magnetic resonance imaging (MRI) findings of five relapsing–remitting MS (RRMS) patients who had clinical relapses characterized by the acute appearance of cortical symptoms, due to the development of large, snake-like, cortical inflammatory lesions. Symptoms were: acute Wernicke's aphasia mimicking stroke; agraphia with acalculia, not associated to a motor deficit nor linguistic disturbance; hyposthenia of the left arm, followed by muscle twitching of the hand, spreading to arm and face; acute onset of left lower limb paroxysmal hypertonia; and temporal lobe status epilepticus, with psychotic symptoms. Conclusions: Cortical relapses may occur in MS. MRI examination in MS should include sequences, such as double inversion recovery (DIR) or phase sensitive inversion recovery (PSIR), that are aimed at visualizing cortical lesions, especially in the presence of symptoms of cortical dysfunction. Our observation further stresses and extends the clinical relevance of cortical pathology in MS.